Leadership at the Intersection of Gender and Race in Healthcare and Science Case Studies and Tools - Laraque-Arena, Danielle; Germain, Lauren; Young, Virginia; Laraque-Ho, Rivers (Taylor & Francis, 2023)
This book takes a case study approach to explore leadership narratives of women in healthcare and science, paying attention to the intersection of gender, identity, and race in each story. Putting forward a new vision and pathway inclusive of the lived experiences and contributions of women worldwide, this text proposes a strength-based approach to meeting leadership challenges. Key themes discussed include leadership redeﬁned by those not identifying as leaders, the inﬂuence of the intersectionality of race and gender on leadership, and the implications for how we teach about leadership in healthcare and science. Grounded in theory that is translated into practice and evidenced by the leadership case studies described, the book draws out useful tools and organizational learnings to support transformation of the landscape of clinical care, education, research and policies healthcare and science. This book is an invaluable reference for leaders at all levels across healthcare and science. It is also of interest to students and academics from gender studies, leadership studies, organization and governance, anthropology, sociology, higher education, public health, social work, nursing and medicine.